Gadolinium-Based Contrast Agents in Kidney Disease: Comprehensive Review and Clinical Practice Guideline Issued by the Canadian Association of Radiologists. Issue 2 (May 2018) - Schieda, Nicola; Blaichman, Jason I.; Costa, Andreu F.; Glikstein, Rafael; Hurrell, Casey; James, Matthew; Jabehdar Maralani, Pejman; Shabana, Wael; Tang, An; Tsampalieros, Anne; van der Pol, Christian; Hiremath, Swapnil
Use of gadolinium-based contrast agents (GBCAs) in renal impairment is controversial, with physician and patient apprehension in acute kidney injury (AKI), chronic kidney disease (CKD), and dialysis because of concerns regarding nephrogenic systemic fibrosis (NSF). The position that GBCAs are absolutely contraindicated in AKI, CKD stage 4 or 5 (estimated glomerular filtration rate [eGFR] <30 mL/min/1.73 m 2 ) and dialysis-dependent patients is outdated, and may limit access to clinically necessary contrast-enhanced MRI examinations. Following a comprehensive review of the literature and reported NSF cases to date, a committee of radiologists and nephrologists developed clinical practice guidelines to assist physicians in making decisions regarding GBCA administrations. In patients with mild-to-moderate CKD (eGFR ≥30 and <60 mL/min/1.73 m 2 ), administration of standard doses of GBCA is safe and no additional precautions are necessary. In patients with AKI, with severe CKD (eGFR <30 mL/min/1.73 m 2 ), or on dialysis, administration of GBCAs should be considered individually and alternative imaging modalities utilized whenever possible. If GBCAs are necessary, newer GBCAs may be administered with patient consent obtained by a physician (or their delegate), citing an exceedingly low risk (much less than 1%) of developing NSF. Standard GBCA dosing should be used; half or quarter dosing is not recommended and repeat injections should be avoided. Dialysis-dependent patients should receive dialysis; however, initiating dialysis or switching from peritoneal to hemodialysis to reduce the risk of NSF is unproven. Use of a macrocyclic ionic instead of macrocyclic nonionic GBCA or macrocyclic instead of newer linear GBCA to further prevent NSF is unproven. Gadopentetate dimeglumine, gadodiamide, and gadoversetamide remain absolutely contraindicated in patients with AKI, with stage 4 or 5 CKD, or on dialysis. The panel agreed that screening for renal disease is important but less critical when using macrocyclic and newer linear GBCAs. Monitoring for and reporting of potential cases of NSF in patients with AKI or CKD who have received GBCAs is recommended.